MEMBANGUN KEPEMIMPINAN UMKM TERPADU PADA SEKTOR PETERNAKAN - Prayitno Prayitno; Tabrani Tabrani; Maikal Soedijarto (Jurnal Ekonomi dan Bisnis, 2018)
This research helps leaders to grow and integrate their efforts from one business to severalrelated businesses, using a longitudinal approach to know for sure the development of anobject, a survey to collect data from a research sample. This research uses longitudinal designin which qualitative and quantitative techniques are used, using the random purpose samplingtechnique, the data collection process using the study cohort. The result of the researchstated that with strong experience and commitment the UMKM perpetrator is able to developindependent business so as to become the business owner and become the leader in that effort,along with the process of experiencing business constraints but can be solved and generatenew businesses that still exist kaitanya with the main business so that the business is combinedand mutually supportive. This study also corroborates research by Rajani and Sarada (2008)which shows a strong influence between leadership on the performance of UMKMKeywords: experience, commitment, leadership umkm